Use Of The UTAUT 2 Model to Find Out Acceptance of Multimodality Learning Media Web-Based Elementary School Teachers in West Java - Susilawati, Erna; Abidin, Yunus; Kurniawan, Dede Trie (PrimaryEdu : Journal of Primary Education, 2023)
Abstract Interest in web-based multimodality learning media has increased rapidly in recent years. Multimodality learning media combines various elements such as text, images, audio, video, animation, and interactivity to create rich and interesting learning experiences. This study aims to describe the success and acceptability of web-based multimodality learning media among students. This study uses a qualitative approach involving students from various levels of education. Data was collected through observation, interviews and surveys. The results showed that web-based multimodality learning media was highly accepted by students. They expressed high satisfaction with interactive multimodality learning experiences and greater involvement in the learning process. Learners appreciate the accessibility of web-based learning media that allows flexible and independent learning. They also reported that the use of various media elements such as images, videos, and audio helps reinforce understanding and maintain interest in learning. Students also like interactive features that allow them to be actively involved in the learning process, such as quizzes, interactive exercises, and online discussions. However, this study also identified several challenges that need to be addressed. Some students experience problems accessing a stable and limited internet, while others have limitations in technology skills. In addition, the attention that is divided between learning media and online distractions is also a challenge faced by students. Referring to the results of this study, it is suggested that educational institutions continue to encourage the use of web-based multimodality learning media. Efforts need to be made to improve internet accessibility and provide technology skills training to students. In addition, it is important to design learning media that are interesting, interactive, and easy to use to maintain students' interest and involvement in the learning process. Keywords: UTAUT2; Instructional Media; Multimodality